Slurry, polishing liquid manufacturing method and polishing method

By using a composite particle slurry of cerium oxide and cerium compound with an Rsp value of 1.60 or above, and combined with filtration technology, the wear and damage caused by coarse particles in semiconductor component manufacturing is solved, and efficient removal and high-speed grinding are achieved.

CN112640051BActive Publication Date: 2025-03-04RESONAC CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201880097107.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-07-26
Filing Date
2018-09-25
Publication Date
2025-03-04
Estimated Expiration
2038-09-25

AI Technical Summary

Technical Problem

During the semiconductor component manufacturing process, a large number of coarse particles exist in the abrasive liquid and slurry, resulting in increased wear damage, and it is difficult for the prior art to effectively remove these coarse particles.

Method used

The slurry containing cerium oxide and cerium compound composite particles was used, and the Rsp value obtained by pulsed NMR measurement was 1.60 or above. The coarse particles were removed by filtration technology to improve the removal rate.

Benefits of technology

The removal rate of coarse particles in filtration is significantly improved, the wear damage is reduced, and the high-speed grinding speed of insulating materials is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002958353900000281
    Figure BDA0002958353900000281
Patent Text Reader

Abstract

The slurry of the present invention is a slurry containing abrasive grains and a liquid medium, wherein the abrasive grains include a first particle and a second particle in contact with the first particle, the first particle contains a cerium oxide, the second particle contains a cerium compound, and the Rsp value calculated by the following formula (1) is 1.60 or more. Formula (1): Rsp = (Tb / Tav)-1; wherein Tav represents the relaxation time (unit: ms) of the slurry obtained by pulse NMR measurement when the content of the abrasive grains is 2.0% by mass, and Tb represents the relaxation time (unit: ms) of the slurry obtained by centrifugal acceleration of 2.36×10 5 G: relaxation time (unit: ms) of the supernatant obtained by pulse NMR measurement when the slurry is centrifuged for 50 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a slurry, a method for producing a grinding liquid and a grinding method. Background Art

[0002] In the manufacturing process of semiconductor elements in recent years, the importance of processing technology for high density and miniaturization has gradually increased. CMP (Chemical Mechanical Polishing) technology, one of the processing technologies, has become an essential technology for the formation of shallow trench isolation (hereinafter referred to as "STI"), planarization of pre-metal insulating materials or interlayer insulating materials, and formation of plugs or buried metal wiring in the manufacturing process of semiconductor elements.

[0003] As the most commonly used polishing liquid, for example, there can be cited a silica-based polishing liquid containing silica (silicon oxide) particles such as fumed silica and colloidal silica as abrasive particles. The silica-based polishing liquid is characterized by high versatility, and can polish a wide range of materials, whether insulating materials or conductive materials, by appropriately selecting the abrasive content, pH, additives, etc.

[0004] On the other hand, as a polishing liquid mainly for insulating materials such as silicon oxide, the demand for polishing liquids containing cerium compound particles as abrasives is also increasing. For example, a cerium oxide-based polishing liquid containing cerium oxide particles as abrasives can polish silicon oxide at a high speed even if the abrasive content is lower than that of a silicon dioxide-based polishing liquid (for example, refer to the following Patent Documents 1 and 2).

[0005] Previous technical literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 10-106994

[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 08-022970

[0009] Patent Document 3: Japanese Patent Application Publication No. 2006-249129

[0010] Patent Document 4: International Publication No. 2012 / 070544 Summary of the invention

[0011] Technical issues to be solved by the invention

[0012] However, in recent years, in the manufacturing process of semiconductor elements, it is required to realize further miniaturization of circuits, and the grinding damage generated during grinding becomes a problem. That is, if there are a large number of coarse particles during grinding, there is a tendency for the grinding damage generated during grinding to increase. Therefore, it is required to reduce the coarse particles in the grinding liquid and the slurry for making the grinding liquid. As a method for removing coarse particles, sedimentation separation, liquid cyclone, filtration, etc. have been studied. From the perspective of having little influence on the characteristics of the grinding liquid and the slurry and excellent reproducibility, there is a tendency to implement filtration.

[0013] However, in the conventional cerium oxide-based polishing liquid, there is a problem of low removal rate (capture efficiency) of coarse particles during filtration. In view of this, in order to improve the removal rate of coarse particles, a method of reducing the pore size of the filter is considered. However, when the pore size of the filter is too small, there are the following problems: the removal rate of coarse particles is reduced due to clogging; or the particle size distribution changes before and after filtration due to the attachment of particles to the filter material, thereby reducing the polishing speed. For this reason, there is a limit to the operation of adjusting the removal rate of coarse particles by selecting a filter (adjusting the pore size of the filter, etc.).

[0014] The present invention aims to solve the above-mentioned problems, and its object is to provide a slurry that can achieve an excellent removal rate of coarse particles in filtration. In addition, the present invention aims to provide a method for producing a polishing liquid using the slurry. Furthermore, the present invention aims to provide a polishing method using a polishing liquid obtained by using the method for producing the polishing liquid.

[0015] Means for solving technical problems

[0016] A slurry according to one aspect of the present invention is a slurry containing abrasive grains and a liquid medium, wherein the abrasive grains include first particles and second particles in contact with the first particles, the first particles contain cerium oxide, the second particles contain a cerium compound, and the Rsp value calculated by the following formula (1) is greater than 1.60.

[0017] Rsp=(Tb / Tav)-1 (1)

[0018] [wherein, Tav represents the relaxation time (unit: ms) of the slurry measured by pulse NMR when the content of the abrasive is 2.0 mass %, and Tb ... 5 G. Relaxation time (unit: ms) of the supernatant obtained by pulse NMR measurement when the slurry is centrifuged for 50 minutes]

[0019] According to the slurry according to one aspect of the present invention, an excellent removal rate of coarse particles during filtration can be obtained. According to such a slurry, coarse particles can be removed by filtration, thereby reducing grinding damage generated during grinding.

[0020] Another aspect of the present invention provides a method for producing a polishing liquid including filtering the slurry. According to the method for producing a polishing liquid, a polishing liquid capable of reducing polishing damage generated during polishing can be obtained.

[0021] Another aspect of the present invention relates to a polishing method including the step of polishing a surface to be polished using a polishing liquid obtained by the method for producing a polishing liquid. According to this polishing method, polishing damage generated during polishing can be reduced.

[0022] Effects of the Invention

[0023] According to the present invention, a slurry that can achieve an excellent removal rate of coarse particles in filtration can be provided. Furthermore, according to the present invention, a method for manufacturing a polishing liquid using the slurry can be provided. Further, according to the present invention, a polishing method using a polishing liquid obtained by using the method for manufacturing the polishing liquid can be provided. According to the present invention, the use of a slurry or a polishing liquid in polishing silicon oxide can be provided. DETAILED DESCRIPTION

[0024] Hereinafter, embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.

[0025] <Definition>

[0026] In this specification, the numerical range represented by "~" represents a range including the numerical values ​​recorded before and after "~" as the minimum and maximum values, respectively. In the numerical range recorded in stages in this specification, the upper limit or lower limit of the numerical range of a certain stage can be arbitrarily combined with the upper limit or lower limit of the numerical range of another stage. In the numerical range recorded in this specification, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiment. The so-called "A or B" can be included as long as any one of A and B is included, or both can be included at the same time. The materials exemplified in this specification can be used alone or in combination of two or more as long as there is no special explanation. In this specification, when there are multiple substances equivalent to each component in the composition, as long as there is no special explanation, the content of each component in the composition refers to the total amount of the multiple substances present in the composition. The term "process" refers not only to an independent process, but also to this term as long as the expected effect of the process can be achieved even if it cannot be clearly distinguished from other processes.

[0027] As described later, the slurry and polishing liquid involved in this embodiment contain abrasive grains. Abrasive grains are also called "abrasive particles", but are referred to as "abrasive grains" in this specification. Abrasive grains are generally considered to be solid particles, and during polishing, the object to be removed is removed by the mechanical action (physical action) of the abrasive grains and the chemical action of the abrasive grains (mainly the surface of the abrasive grains), but it is not limited to this.

[0028] The term "polishing liquid" (abrasive) is defined as a composition that comes into contact with the surface being polished during polishing. The term "polishing liquid" itself does not limit the components contained in the polishing liquid.

[0029] The weight average molecular weight in this specification can be measured by gel permeation chromatography (GPC) under the following conditions using a calibration curve of standard polystyrene, for example.

[0030] Equipment used: Hitachi L-6000 [manufactured by Hitachi, Ltd.]

[0031] Column: Gel pack GL-R420 + Gel pack GL-R430 + Gel pack GL-R440 [manufactured by Hitachi Chemical Co., Ltd., trade name, 3 pieces in total]

[0032] Eluent: Tetrahydrofuran

[0033] Measurement temperature: 40℃

[0034] Flow rate: 1.75mL / min

[0035] Detector: L-3300RI [manufactured by Hitachi, Ltd.]

[0036] The so-called "coarse particles" refer to particulate substances that are significantly larger in the particle size distribution of abrasive particles in a slurry or a polishing liquid. The material of the coarse particles is not particularly limited, and examples thereof include coarse crystals or particle agglomerates, foreign matter mixed from the outside, and complexes of these. The shape of the coarse particles is not particularly limited, and may be spherical, rod-shaped, etc., or may be a shape with a large aspect ratio, or may be a shape with bumps on the surface. The lower limit of the size (particle size) of the coarse particles is, for example, 3 μm. Among them, as long as an excellent removal rate of coarse particles can be obtained, the lower limit of the size of the coarse particles may also be, for example, 0.5 μm, 1 μm, 2 μm, etc.

[0037] <Slurry, polishing liquid, and method for producing the same>

[0038] The slurry involved in this embodiment contains abrasive grains and a liquid medium as essential components. The abrasive grains contain composite particles, and the composite particles include a first particle and a second particle in contact with the first particle. The first particle contains cerium oxide, and the second particle contains a cerium compound. In the slurry of this embodiment, the Rsp value calculated by the following formula (1) is 1.60 or more.

[0039] Rsp=(1 / Tav-1 / Tb)×(Tb)=(Tb / Tav)-1 (1)

[0040] [wherein, Tav represents the relaxation time (unit: ms) of the slurry measured by pulse NMR when the content of the abrasive is 2.0 mass %, and Tb represents the relaxation time (unit: ms) of the slurry measured by pulse NMR when the content of the abrasive is 2.0 mass %, and ... 5 G Relaxation time (unit: ms) of the supernatant obtained by pulse NMR measurement when the slurry is centrifuged for 50 minutes]

[0041] By filtering the slurry involved in the present embodiment, an excellent removal rate of coarse particles can be obtained. According to this slurry, the coarse particles are removed by filtering, thereby reducing the grinding damage caused during grinding. When the removal rate of coarse particles is large, there is a tendency to easily reduce the number of coarse particles, which can effectively reduce the grinding damage. As the reason for obtaining an excellent removal rate of coarse particles in this way, for example, the following reasons can be cited. Among them, the reasons are not limited to the following.

[0042] That is, it is presumed that when the second particle containing the cerium compound contacts the first particle containing the cerium oxide, an attractive interaction occurs between the particles. Such interaction is not particularly limited, and examples thereof include electrostatic attraction, covalent bonds, van der Waals forces, dipole-dipole interactions, hydrophobic bonds, hydrogen bonds, and depletion effects caused by concentration differences of polymers or nanoparticles. It is generally believed that the above interactions lead to agglomeration of particles in conventional slurries, thereby increasing the number of coarse particles.

[0043] In this regard, the composite particles in the present embodiment can maintain a dispersed state even if they interact with each other. It is speculated that the reason is that a repulsive interaction is generated between the second particles. That is, other second particles (particles that are not in contact with the first particle, etc.) are difficult to approach the second particle in contact with the first particle. Therefore, new adsorption of the second particle is suppressed, and it is speculated that no coarse agglomerates will be formed. Relative to the gravitational interaction between the first particle and the second particle, the repulsive interaction between the second particles is sufficiently large, and it is speculated that the composite particles in the present embodiment can maintain a dispersed state. The above-mentioned repulsive interaction is not particularly limited, and electrostatic repulsion, osmotic pressure, and steric repulsion based on a surface adsorption layer can be cited.

[0044] On the other hand, about coarse particles, it is speculated that the balance of the above-mentioned opposite interactions is different from that of composite particles. Here, it is known that about the gravitational interaction (Van der Waals force, etc.) that inevitably plays a role between particles, the larger the particle size becomes, the more it increases. Therefore, about the coarse particles with large particle size, other particles are easily adsorbed, and it is difficult to show the inhibitory effect of the condensation based on the repulsive interaction between the second particles. That is, even if the coarse particles are coated by the second particle, the second particle can also be adsorbed continuously. Therefore, it is speculated that the coarse particles with large particle size are adsorbed by the first particle, the second particle or these agglomerates. In this way, the particle size of coarse particles selectively increases, so it is speculated that the coarse particles are captured by the filter material, and the removal rate of coarse particles is easily improved.

[0045] Furthermore, in the present embodiment, when the Rsp value is equal to or greater than the above-mentioned predetermined value, an excellent removal rate of coarse particles can be obtained for the following reasons.

[0046] In pulse NMR measurement, the time (relaxation time) until the nuclear spin that obtains energy by irradiating the molecule with radio waves returns to the original thermal equilibrium state is measured. It is generally known that the slower the molecular motion, the shorter the relaxation time. Here, in the slurry containing abrasives, there are water molecules (bound water) on the surface of the abrasive that interact with the molecules on the surface of the abrasive. Moreover, the water molecules form hydrogen bonds with the first particle or the second particle of the composite particle due to their large polarity, thereby thermally stabilizing. In this case, the molecular motion of the bound water present on the surface of the abrasive is restricted, so compared with the relaxation time of water molecules (free water) that are not in contact with the abrasive and are in a free state, the relaxation time of the bound water is shorter. Here, the relaxation time Tav obtained in the pulse NMR measurement represents the average value of the relaxation time reflecting the volume of the bound water present on the surface of the abrasive and the relaxation time reflecting the volume of the free water. Therefore, the larger the volume of bound water is compared to the volume of free water (i.e., the stronger the interaction between the molecules on the surface of the abrasive and the water molecules (the higher the affinity)), the shorter Tav becomes, and as a result, the larger the Rsp value obtained by the above formula (1). In other words, it can be said that the larger the Rsp value, the higher the hydrophilicity of the abrasive.

[0047] When the slurry is filtered using a filter, the coarse particles are captured and removed by the fine pores (pores) present in the filter material of the filter. On the other hand, the liquid medium penetrates into the pores of the filter material through capillary action. The so-called capillary action refers to the phenomenon that the liquid penetrates into a small space surrounded by a solid. The higher the wettability of the solid relative to the liquid (the degree of affinity of the solid relative to the liquid), the easier it is for the liquid to penetrate into the space. Usually, the size of the pores in the filter material is not uniform, and it is difficult for the slurry to enter the fine pores. In particular, when the surface of the filter material is hydrophobic, the wettability of the filter material relative to water is small, so it is difficult for the slurry to penetrate into the pores. In this case, the slurry passes through the pores with relatively large pore sizes in the pores in the filter material, so the coarse particles are easy to pass through the pores, so the removal rate of the coarse particles is reduced.

[0048] According to the inventor's inference, when a slurry containing abrasive grains with high hydrophilicity (i.e., a slurry with a large Rsp value) is passed through a filter, if the abrasive grains are attached to the surface of the filter material, the surface of the filter material is hydrophilic because the abrasive grains themselves are hydrophilic, and the wettability of the filter material relative to water is improved. As a result, the slurry easily penetrates into the pores, and the coarse particles are easily captured, so the removal rate of the coarse particles is improved. Based on the above reasons, the removal rate of the coarse particles can be improved by setting the Rsp value to be greater than the above-mentioned specified value.

[0049] However, it is considered to avoid the generation of coarse particles and the mixing of coarse particles into slurry and grinding liquid by adjusting the preparation method of particles. For example, the method for liquid phase synthesis of microparticles is easy to reduce the mixing of coarse particles compared with the method of crushing and miniaturizing polycrystalline (for example, polycrystalline of cerium oxide) particles. However, in this method, in order to prevent the unexpected generation of coarse particles, it is necessary to miniaturize the particles by optimizing the manufacturing conditions of particles. In this case, if the crystallite diameter of the particle is small, it is difficult to obtain mechanical grinding, so there is a tendency that the grinding speed is reduced, and it is difficult to effectively reduce coarse particles and to achieve the high-speed grinding speed of insulating materials.

[0050] On the other hand, according to this embodiment, coarse particles can be effectively reduced and a high polishing speed of an insulating material (e.g., silicon oxide) can be achieved. As a reason for increasing the polishing speed of the insulating material, for example, the following reasons can be cited. Among them, the reasons are not limited to the following.

[0051] That is, the first particle containing cerium oxide and having a particle size larger than that of the second particle has a stronger mechanical effect (mechanical property) on the insulating material than the second particle. On the other hand, the second particle containing a cerium compound and having a particle size smaller than that of the first particle has a smaller mechanical effect on the insulating material than the first particle, but because the specific surface area (surface area per unit mass) of the entire particle is large, the chemical effect (chemical property) on the insulating material is strong. In this way, by using the first particle with a strong mechanical effect and the second particle with a strong chemical effect, it is easy to obtain a synergistic effect of increasing the polishing speed. As a result, a high-speed polishing speed of the insulating material can be achieved.

[0052] According to this embodiment, a high grinding speed of the insulating material can be achieved, so by adjusting the content of the abrasive to be smaller, coarse particles can also be reduced. In addition, generally, as the content of the abrasive increases, there is a tendency to easily generate grinding damage. On the other hand, according to this embodiment, a sufficient grinding speed can be obtained even when the content of the abrasive is small, so by using a small amount of abrasive, a sufficient grinding speed can be achieved and the insulating material can be ground with low grinding damage.

[0053] As described above, in the slurry involved in this embodiment, the relaxation time Tav and relaxation time Tb obtained by pulse NMR measurement (pulse nuclear magnetic resonance measurement) and the Rsp value calculated by formula (1) are 1.60 or more. Pulse NMR measurement is to measure the hydrogen nuclei ( 1The method for measuring the transverse relaxation time of the H nucleus can be performed using a pulsed NMR particle interface characteristic evaluation device (trade name: Acron Area) manufactured by Rufuto Co., Ltd. of Japan. The relaxation time can be obtained using the Carr Purcell Meiboom Gill method (CPMG method). The measurement temperature is 25°C. The Rsp value is an index of the affinity between the particles and water molecules, and can be calculated using the relaxation time Tav of the slurry and the relaxation time Tb of the supernatant obtained when the slurry is centrifuged and calculated by the above formula (1).

[0054] From the perspective of obtaining an excellent removal rate of coarse particles, the Rsp value is 1.60 or more. From the perspective of easily obtaining an excellent removal rate of coarse particles, the lower limit of the Rsp value is preferably 1.80 or more, more preferably 2.00 or more, more preferably 2.20 or more, and particularly preferably 2.40 or more. The upper limit of the Rsp value may be, for example, 10.0 or less.

[0055] The more bound water there is on the surface of the abrasive, the larger the Rsp value becomes. Therefore, the larger the surface area of ​​the abrasive that can adsorb bound water, the easier it is for the Rsp value to become larger. Therefore, for example, by changing the particle size (average primary particle size or average secondary particle size) of the first particle and / or the second particle in the composite particle, the Rsp value can be adjusted. Alternatively, the Rsp value can also be increased by hydrophilizing the surface of the abrasive. As a method for hydrophilizing, for example, a method of coating the surface of the abrasive with a compound having a functional group (for example, a carboxyl group) with high affinity for water and a method of surface modifying the abrasive using the compound can be cited.

[0056] The polishing liquid (CMP polishing liquid) according to the present embodiment can be obtained, for example, by filtering the slurry according to the present embodiment. The method for producing the polishing liquid according to the present embodiment includes a filtering step of filtering the slurry according to the present embodiment.

[0057] In the filtering process, a filter (filter material) can be used to remove coarse particles. The shape of the filter is not particularly limited, and examples thereof include a disc type, a cartridge type, etc. From the perspective of improving liquid permeability, a cartridge type filter can also be processed into a pleated shape.

[0058] Examples of the material constituting the filter include polypropylene, nylon, glass, polyester, polyethersulfone, polytetrafluoroethylene, polycarbonate, polyvinylidene fluoride, and cellulose derivatives, etc. These materials can be processed into a membrane or fiber form.

[0059] The pore size (nominal pore size) of the filter is preferably in the following range. From the viewpoint of excellent filtration speed, the viewpoint that the particle size distribution is difficult to change, and the viewpoint of excellent filter life (the effect of preventing clogging), the lower limit of the pore size of the filter is preferably 0.10 μm or more, and more preferably 0.20 μm or more. From the viewpoint of easily obtaining an excellent removal rate of coarse particles, the upper limit of the pore size of the filter is preferably 3.0 μm or less, more preferably 2.0 μm or less, further preferably 1.0 μm or less, particularly preferably 0.80 μm or less, and extremely preferably 0.50 μm or less. From the above viewpoint, the pore size of the filter is preferably 0.10 to 3.0 μm.

[0060] The filtration can be carried out in one stage or in multiple stages by combining multiple filters. Furthermore, the slurry can be passed through a single filter once or the same filter can be cycled multiple times.

[0061] (Abrasive particles)

[0062] As described above, the abrasive in this embodiment includes composite particles including first particles and second particles in contact with the first particles.

[0063] The particle diameter of the second particle is preferably smaller than the particle diameter of the first particle. The size relationship of the particle diameter of the first particle and the second particle can be distinguished according to the SEM image of composite particles etc. Usually, in the particle with little particle diameter, compared with the particle with large particle diameter, the surface area per unit mass is large, so the reactivity is high. On the other hand, compared with the particle with large particle diameter, the mechanical action (mechanical grinding force) of the particle with small particle diameter is small. But, in the present embodiment, even when the particle diameter of the second particle is less than the particle diameter of the first particle, the synergistic effect of the first particle and the second particle can be shown, and excellent reactivity and mechanical action can be easily taken into account.

[0064] From the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the particle size of the first particle is preferably 15 nm or more, more preferably 25 nm or more, more preferably 35 nm or more, especially preferably 40 nm or more, extremely preferably 50 nm or more, very preferably 80 nm or more, and more preferably 100 nm or more. From the viewpoint of improving the dispersibility of the abrasive and easily suppressing damage to the polished surface, the upper limit of the particle size of the first particle is preferably 1000 nm or less, more preferably 800 nm or less, more preferably 600 nm or less, especially preferably 400 nm or less, extremely preferably 300 nm or less, very preferably 200 nm or less, and more preferably 150 nm or less. From the viewpoint of the above, the particle size of the first particle is more preferably 15 to 1000 nm. The average particle size (average secondary particle size) of the first particle may also be within the above range.

[0065] From the viewpoint of further improving the grinding speed of the insulating material, the lower limit of the particle size of the second particle is preferably 1 nm or more, more preferably 2 nm or more, and more preferably 3 nm or more. From the viewpoint of improving the dispersibility of the abrasive and easily suppressing damage to the polished surface, the upper limit of the particle size of the second particle is preferably 50 nm or less, more preferably 30 nm or less, more preferably 25 nm or less, particularly preferably 20 nm or less, extremely preferably 15 nm or less, and very preferably 10 nm or less. From the viewpoint of the above, the particle size of the second particle is more preferably 1 to 50 nm. The average particle size (average secondary particle size) of the second particle may also be within the above range.

[0066] The average particle size (average secondary particle size) of the abrasive (including the abrasive of the composite particles as a whole) in the slurry or polishing liquid is preferably in the following range. From the perspective of further improving the polishing speed of the insulating material, the lower limit of the average particle size of the abrasive is preferably 16 nm or more, more preferably 20 nm or more, more preferably 30 nm or more, especially preferably 40 nm or more, extremely preferably 50 nm or more, very preferably 100 nm or more, further preferably 120 nm or more, more preferably 140 nm or more, particularly preferably 150 nm or more, and extremely preferably 155 nm or more. From the perspective of the particle size distribution being difficult to change, the perspective of improving the dispersibility of the abrasive, and the perspective of easily suppressing damage to the polished surface, the upper limit of the average particle size of the abrasive is preferably 1050 nm or less, more preferably 1000 nm or less, further preferably 800 nm or less, especially preferably 600 nm or less, extremely preferably 500 nm or less, very preferably 400 nm or less, further preferably 300 nm or less, more preferably 200 nm or less, and especially preferably 160 nm or less. From this viewpoint, the average particle size of the abrasive grains is more preferably 16 to 1050 nm.

[0067] The average particle size can be measured using, for example, a light diffraction scattering type particle size distribution analyzer (for example, N5 manufactured by Beckman Coulter Co., Ltd., or Microtrac MT3300EXII manufactured by Microtrac BEL Co., Ltd.).

[0068] The first particle can have a negative zeta potential. The second particle can have a positive zeta potential. The so-called zeta potential represents the surface potential of the particle. The zeta potential can be measured, for example, using a dynamic light scattering zeta potential measuring device (for example, manufactured by Beckman Coulter Co., Ltd., trade name: DelsaNano C). The zeta potential of the particle can be adjusted using an additive. For example, by contacting ammonium dihydrogen phosphate, a material having a carboxyl group (for example, polyacrylic acid), etc. with particles containing cerium oxide, particles having a negative zeta potential can be obtained.

[0069] The first particle contains cerium oxide (for example, cerium dioxide), and the second particle contains a cerium compound. Examples of the cerium compound of the second particle include cerium hydroxide and cerium oxide. As the cerium compound of the second particle, a compound different from cerium oxide can be used. The cerium compound preferably contains cerium hydroxide. Compared with particles composed of silicon dioxide, cerium oxide, etc., abrasive particles containing cerium hydroxide have a higher reactivity (chemical reaction) with insulating materials (for example, silicon oxide) through the action of hydroxyl groups, and can grind insulating materials at a higher grinding speed. Cerium hydroxide, for example, contains tetravalent cerium (Ce 4 + ) and at least one hydroxide ion (OH - ) compounds. Cerium hydroxide may also contain anions other than hydroxide ions (e.g., nitrate ions NO3 - and sulfate ion SO4 2- For example, the cerium hydroxide may also include an anion (e.g., a nitrate ion, NO3) bonded to tetravalent cerium. - and sulfate ion SO4 2- ).

[0070] Cerium hydroxide can be made by reacting a cerium salt with an alkali source (base). Cerium hydroxide is preferably made by mixing a cerium salt with an alkali solution (e.g., an alkaline aqueous solution). Thus, particles with extremely fine particle size can be obtained, and it is easy to obtain an excellent reduction effect of grinding damage. This method is disclosed in, for example, Patent Document 3 and Patent Document 4. Cerium hydroxide can be obtained by mixing a cerium salt solution (e.g., an aqueous cerium salt solution) with an alkali solution. As cerium salts, Ce(NO3)4, Ce(SO4)2, Ce(NH4)2(NO3)6, Ce(NH4)4(SO4)4, etc. can be listed.

[0071] It is believed that the production conditions of cerium hydroxide may lead to the formation of Ce(OH) a X b (where a+b×c=4) (in addition, such particles are also cerium hydroxide), the Ce(OH) a X b The tetravalent cerium (Ce4+ ), 1 to 3 hydroxide ions (OH - ) and 1 to 3 anions (X c- ) is composed. And it is believed that in Ce(OH) a X b In the case of electron-withdrawing anions (X c- ) plays a role in increasing the reactivity of hydroxide ions, and as Ce(OH) a X b As the amount of anion (X c- ), for example, NO3 - and SO4 2- It is believed that the particles containing cerium hydroxide may contain not only Ce(OH) a X b , and may also contain Ce(OH)4, CeO2, etc.

[0072] Regarding the particles containing cerium hydroxide containing Ce(OH) a X b The following method can be used to confirm that the particles are fully washed with pure water and then the anions (X c- ) peak. The XPS method (X-ray Photoelectron Spectroscopy) can also be used to confirm the anion (X c- )’s existence.

[0073] Composite particles comprising a first particle and a second particle can be obtained by the following methods, etc.: bringing the first particle into contact with the second particle using a homogenizer, a high-pressure homogenizer (nanomizer), a ball mill, a bead mill, an ultrasonic processor, etc.; bringing the first particle having opposite charges to each other into contact with the second particle; and bringing the first particle into contact with the second particle in a state where the content of the particles is small.

[0074] According to this embodiment, there can be provided a method for producing abrasive grains, including the step of bringing first particles containing cerium oxide into contact with second particles containing cerium compounds. According to this embodiment, there can be provided a method for producing slurry, including the step of obtaining abrasive grains using the method for producing abrasive grains.

[0075] From the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the content of cerium oxide in the first particle is based on the first particle as a whole (the first particle as a whole contained in the slurry or the polishing liquid. The same applies hereinafter), preferably 50 mass % or more, more preferably 70 mass % or more, further preferably 90 mass % or more, and particularly preferably 95 mass % or more. The first particle may also be substantially composed of cerium oxide (substantially 100 mass % of the first particle is cerium oxide).

[0076] From the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the content of the cerium compound in the second particle is based on the second particle as a whole (the second particle as a whole contained in the slurry or the polishing liquid. The same below), preferably 50 mass % or more, more preferably 70 mass % or more, further preferably 90 mass % or more, and particularly preferably 95 mass % or more. The second particle can also be substantially composed of a cerium compound (substantially 100 mass % of the second particle is a cerium compound).

[0077] By using the value of the absorbance of the following formula obtained by using a spectrophotometer when making the light of a specific wavelength pass through the slurry or the polishing liquid, the content of the second particle can be inferred. That is, when the particle absorbs the light of a specific wavelength, the transmittance of the region containing the particle decreases. The transmittance is not only reduced by the absorption of the particle, but also reduced by scattering, but in the second particle, the influence of scattering is small. Therefore, in the present embodiment, the content of the second particle can be inferred by using the value of the absorbance calculated by the following formula.

[0078] Absorbance = -LOG 10 (Transmittance [%] / 100)

[0079] The content of the first particle in the abrasive is preferably in the following range based on the overall abrasive (the overall abrasive contained in the slurry or polishing liquid). From the perspective of further improving the polishing speed of the insulating material, the lower limit of the content of the first particle is preferably 50% by mass or more, more preferably more than 50% by mass, more preferably more than 60% by mass, especially preferably more than 70% by mass, extremely preferably more than 75% by mass, very preferably more than 80% by mass, and even more preferably more than 85% by mass. From the perspective of further improving the polishing speed of the insulating material, the upper limit of the content of the first particle is preferably 97% by mass or less, more preferably 95% by mass or less, more preferably 93% by mass or less, especially preferably 90% by mass or less, extremely preferably 88% by mass or less, and very preferably 86% by mass or less. From the perspective of the above, the content of the first particle is more preferably 50 to 97% by mass.

[0080] The content of the second particles in the abrasive is preferably in the following range based on the overall abrasive (the overall abrasive contained in the slurry or polishing liquid). From the perspective of further improving the polishing speed of the insulating material, the lower limit of the content of the second particles is preferably 3% by mass or more, more preferably 5% by mass or more, more preferably 7% by mass or more, especially preferably 10% by mass or more, extremely preferably 12% by mass or more, and very preferably 14% by mass or more. From the perspective of further improving the polishing speed of the insulating material, the upper limit of the content of the second particles is preferably 50% by mass or less, more preferably less than 50% by mass, more preferably 40% by mass or less, especially preferably 30% by mass or less, extremely preferably 25% by mass or less, very preferably 20% by mass or less, and even more preferably 15% by mass or less. From the perspective of the above, the content of the second particles is more preferably 3 to 50% by mass.

[0081] The content of cerium oxide in the abrasive is preferably in the following range based on the whole abrasive (the whole abrasive contained in the slurry or the polishing liquid). From the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the content of cerium oxide is preferably 50% by mass or more, more preferably more than 50% by mass, more preferably more than 60% by mass, especially preferably more than 70% by mass, extremely preferably more than 75% by mass, very preferably more than 80% by mass, and even more preferably more than 85% by mass. From the viewpoint of further improving the polishing speed of the insulating material, the upper limit of the content of cerium oxide is preferably 97% by mass or less, more preferably 95% by mass or less, more preferably 93% by mass or less, especially preferably 90% by mass or less, extremely preferably 88% by mass or less, and very preferably 86% by mass or less. From the viewpoint of further improving the polishing speed of the insulating material, the content of cerium oxide is more preferably 50 to 97% by mass.

[0082] The content of cerium hydroxide in the abrasive is preferably in the following range based on the whole abrasive (the whole abrasive contained in the slurry or polishing liquid). From the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the content of cerium hydroxide in the abrasive is preferably 3% by mass or more, more preferably 5% by mass or more, more preferably 7% by mass or more, especially preferably 10% by mass or more, extremely preferably 12% by mass or more, and very preferably 14% by mass or more. From the viewpoint of further improving the polishing speed of the insulating material, the upper limit of the content of cerium hydroxide in the abrasive is preferably 50% by mass or less, more preferably less than 50% by mass, more preferably 40% by mass or less, especially preferably 30% by mass or less, extremely preferably 25% by mass or less, very preferably 20% by mass or less, and further preferably 15% by mass or less. From the viewpoint of further improving the polishing speed of the insulating material, the content of cerium hydroxide in the abrasive is more preferably 3 to 50% by mass.

[0083] The content of the first particle in the slurry or polishing liquid is preferably in the following range based on the total amount of the first particle and the second particle. From the perspective of further improving the polishing speed of the insulating material, the lower limit of the content of the first particle is preferably 50% by mass or more, more preferably more than 50% by mass, more preferably more than 60% by mass, especially preferably more than 70% by mass, extremely preferably more than 75% by mass, very preferably more than 80% by mass, and even more preferably more than 85% by mass. From the perspective of further improving the polishing speed of the insulating material, the upper limit of the content of the first particle is preferably less than 97% by mass, more preferably less than 95% by mass, more preferably less than 93% by mass, especially preferably less than 90% by mass, extremely preferably less than 88% by mass, and very preferably less than 86% by mass. From the perspective of the above, the content of the first particle is more preferably 50 to 97% by mass.

[0084] The content of the second particle in the slurry or polishing liquid is preferably in the following range based on the total amount of the first particle and the second particle. From the perspective of further improving the polishing speed of the insulating material, the lower limit of the content of the second particle is preferably 3% by mass or more, more preferably 5% by mass or more, more preferably 7% by mass or more, especially preferably 10% by mass or more, extremely preferably 12% by mass or more, and very preferably 14% by mass or more. From the perspective of further improving the polishing speed of the insulating material, the upper limit of the content of the second particle is preferably 50% by mass or less, more preferably less than 50% by mass, more preferably 40% by mass or less, especially preferably 30% by mass or less, extremely preferably 25% by mass or less, very preferably 20% by mass or less, and even more preferably 15% by mass or less. From the perspective of the above, the content of the second particle is more preferably 3 to 50% by mass.

[0085] The content of the first particle in the slurry is preferably in the following range based on the total mass of the slurry. From the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the content of the first particle is preferably 0.05 mass % or more, more preferably 0.08 mass % or more, more preferably 0.1 mass % or more, especially preferably 0.5 mass % or more, extremely preferably 0.8 mass % or more, and very preferably 1 mass % or more. From the viewpoint of improving the storage stability of the slurry, the upper limit of the content of the first particle is preferably 10 mass % or less, more preferably 8 mass % or less, further preferably 5 mass % or less, especially preferably 4 mass % or less, extremely preferably 3 mass % or less, and very preferably 2 mass % or less. From the viewpoint, the content of the first particle is more preferably 0.05 to 10 mass %.

[0086] The content of the first particle in the polishing liquid is preferably in the following range based on the total mass of the polishing liquid. With respect to further improving the polishing speed of the insulating material, the lower limit of the content of the first particle is preferably 0.005 mass % or more, more preferably 0.008 mass % or more, more preferably 0.01 mass % or more, especially preferably 0.05 mass % or more, extremely preferably 0.07 mass % or more, and very preferably 0.08 mass % or more. With respect to improving the storage stability of the polishing liquid and easily suppressing the damage to the polished surface, the upper limit of the content of the first particle is preferably 10 mass % or less, more preferably 5 mass % or less, more preferably 1 mass % or less, especially preferably 0.5 mass % or less, extremely preferably 0.3 mass % or less, very preferably 0.2 mass % or less, and further preferably 0.1 mass % or less. With respect to the above viewpoint, the content of the first particle is more preferably 0.005-1 mass %.

[0087] The content of the second particles in the slurry is preferably in the following range based on the total mass of the slurry. From the perspective of further improving the chemical interaction between the abrasive and the polished surface and further improving the polishing speed of the insulating material, the lower limit of the content of the second particles is preferably 0.05 mass % or more, more preferably 0.1 mass % or more, more preferably 0.15 mass % or more, especially preferably 0.2 mass % or more, extremely preferably 0.25 mass % or more, very preferably 0.275 mass % or more, further more preferably 0.3 mass % or more, more preferably 0.325 mass % or more, especially preferably 0.35 mass % or more. From the perspective of easily avoiding the aggregation of abrasive particles, and the chemical interaction between the abrasive and the polished surface is better, and it is easy to effectively utilize the characteristics of the abrasive particles, the upper limit of the content of the second particles is preferably 5 mass % or less, more preferably 3 mass % or less, more preferably 1 mass % or less, especially preferably 0.5 mass % or less, and extremely preferably 0.4 mass % or less. From the perspective of the above, the content of the second particles is more preferably 0.05-5 mass %.

[0088] The content of the second particle in the polishing liquid is preferably the following range based on the total mass of the polishing liquid. With respect to the viewpoint of further improving the chemical interaction between the abrasive grains and the polished surface and further improving the polishing speed of the insulating material, the lower limit of the content of the second particle is preferably 0.001 mass % or more, more preferably 0.003 mass % or more, more preferably 0.005 mass % or more, especially preferably 0.008 mass % or more, extremely preferably 0.01 mass % or more, very preferably 0.012 mass % or more, and further more preferably 0.014 mass % or more. With respect to the viewpoint of easily avoiding the agglomeration of abrasive grains and the chemical interaction between the abrasive grains and the polished surface is better, and it is easy to effectively utilize the characteristics of abrasive grains, the upper limit of the content of the second particle is preferably 1 mass % or less, more preferably 0.5 mass % or less, further preferably 0.1 mass % or less, especially preferably 0.05 mass % or less, extremely preferably 0.03 mass % or less, very preferably 0.02 mass % or less, and further more preferably 0.015 mass % or less. From this viewpoint, the content of the second particles is more preferably 0.001 to 1% by mass.

[0089] The content of cerium oxide in the slurry is preferably in the following range based on the total mass of the slurry. From the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the content of cerium oxide is preferably 0.05 mass % or more, more preferably 0.08 mass % or more, more preferably 0.1 mass % or more, especially preferably 0.5 mass % or more, extremely preferably 0.8 mass % or more, and very preferably 1 mass % or more. From the viewpoint of improving the storage stability of the slurry, the upper limit of the content of cerium oxide is preferably 10 mass % or less, more preferably 8 mass % or less, further preferably 5 mass % or less, especially preferably 4 mass % or less, extremely preferably 3 mass % or less, and very preferably 2 mass % or less. From the viewpoint of the above, the content of cerium oxide is more preferably 0.05 to 10 mass %.

[0090] The content of cerium oxide in the polishing liquid is preferably in the following range based on the total mass of the polishing liquid. With respect to the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the content of cerium oxide is preferably 0.005 mass % or more, more preferably 0.008 mass % or more, more preferably 0.01 mass % or more, especially preferably 0.05 mass % or more, extremely preferably 0.07 mass % or more, and very preferably 0.08 mass % or more. With respect to the viewpoint of improving the storage stability of the polishing liquid and the viewpoint of easily suppressing damage to the polished surface, the upper limit of the content of cerium oxide is preferably 10 mass % or less, more preferably 5 mass % or less, more preferably 1 mass % or less, especially preferably 0.5 mass % or less, extremely preferably 0.3 mass % or less, very preferably 0.2 mass % or less, and further preferably 0.1 mass % or less. With respect to the above viewpoint, the content of cerium oxide is more preferably 0.005-1 mass %.

[0091] The content of cerium hydroxide in the slurry is preferably in the following range based on the total mass of the slurry. From the perspective of further improving the chemical interaction between the abrasive and the polished surface and further improving the polishing speed of the insulating material, the lower limit of the content of cerium hydroxide is preferably 0.05 mass % or more, more preferably 0.1 mass % or more, more preferably 0.15 mass % or more, especially preferably 0.2 mass % or more, extremely preferably 0.25 mass % or more, very preferably 0.275 mass % or more, further preferably 0.3 mass % or more, more preferably 0.325 mass % or more, especially preferably 0.35 mass % or more. From the perspective of easily avoiding the aggregation of abrasive grains, and the chemical interaction between the abrasive grains and the polished surface is better, and it is easy to effectively utilize the characteristics of the abrasive grains, the upper limit of the content of cerium hydroxide is preferably 5 mass % or less, more preferably 3 mass % or less, more preferably 1 mass % or less, especially preferably 0.5 mass % or less, and extremely preferably 0.4 mass % or less. From the perspective of the above, the content of cerium hydroxide is more preferably 0.05 to 5 mass %.

[0092] The content of cerium hydroxide in the grinding liquid is preferably in the following range based on the total mass of the grinding liquid. With respect to the viewpoint of further improving the chemical interaction between the abrasive grains and the polished surface and further improving the polishing speed of the insulating material, the lower limit of the content of cerium hydroxide is preferably 0.001 mass % or more, more preferably 0.003 mass % or more, more preferably 0.005 mass % or more, especially preferably 0.008 mass % or more, extremely preferably 0.01 mass % or more, very preferably 0.012 mass % or more, and further more preferably 0.014 mass % or more. With respect to the viewpoint of easily avoiding the agglomeration of abrasive grains and the chemical interaction between the abrasive grains and the polished surface is better, and it is easy to effectively utilize the characteristics of abrasive grains, the upper limit of the content of cerium hydroxide is preferably 1 mass % or less, more preferably 0.5 mass % or less, further preferably 0.1 mass % or less, especially preferably 0.05 mass % or less, extremely preferably 0.03 mass % or less, very preferably 0.02 mass % or less, and further more preferably 0.015 mass % or less. From this viewpoint, the content of the cerium hydroxide is more preferably 0.001 to 1% by mass.

[0093] The content of abrasive grains in the slurry is preferably in the following range based on the total mass of the slurry. From the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the content of abrasive grains is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, more preferably 0.1% by mass or more, especially preferably 0.5% by mass or more, extremely preferably 1% by mass or more, very preferably 1.5% by mass or more, further more preferably 2% by mass or more, more preferably 2.1% by mass or more, especially preferably 2.2% by mass or more, extremely preferably 2.3% by mass or more, and very preferably 2.35% by mass or more. From the viewpoint of improving the storage stability of the slurry, the upper limit of the content of abrasive grains is preferably 10% by mass or less, more preferably 8% by mass or less, further preferably 5% by mass or less, especially preferably 4% by mass or less, and extremely preferably 3% by mass or less. From the viewpoint, the content of abrasive grains is more preferably 0.01 to 10% by mass.

[0094] The content of abrasive grains in the polishing liquid is preferably in the following range based on the total mass of the polishing liquid. With respect to further improving the polishing speed of the insulating material, the lower limit of the content of abrasive grains is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, more preferably 0.03% by mass or more, especially preferably 0.05% by mass or more, extremely preferably 0.08% by mass or more, and very preferably 0.1% by mass or more. With respect to improving the storage stability of the polishing liquid and easily suppressing damage to the polished surface, the upper limit of the content of abrasive grains is preferably 10% by mass or less, more preferably 5% by mass or less, more preferably 3% by mass or less, especially preferably 1% by mass or less, extremely preferably 0.5% by mass or less, very preferably 0.3% by mass or less, and further preferably 0.2% by mass or less. With respect to the above viewpoint, the content of abrasive grains is more preferably 0.01 to 10% by mass.

[0095] The slurry or polishing liquid involved in this embodiment may also contain other particles besides the composite particles including the first particles and the second particles. Such other particles include, for example: the first particles not in contact with the second particles; the second particles not in contact with the first particles; and third particles (not including the first particles and the second particles) composed of silicon dioxide, aluminum oxide, zirconium oxide, yttrium oxide, etc.

[0096] (Liquid medium)

[0097] The liquid medium is not particularly limited, and is preferably water such as deionized water and ultrapure water. The content of the liquid medium may be the remainder of the slurry or polishing liquid excluding the contents of other components, and is not particularly limited.

[0098] (Optional ingredient)

[0099] The slurry or polishing liquid involved in the present embodiment may further contain any additive. As any additive, materials having a carboxyl group (excluding compounds equivalent to polyoxyalkylene compounds or water-soluble polymers), polyoxyalkylene compounds, water-soluble polymers, oxidants (e.g., hydrogen peroxide), dispersants (e.g., phosphoric acid-based inorganic salts), etc. may be listed. Each additive may be used alone or in combination of two or more.

[0100] Examples of materials having a carboxyl group include monocarboxylic acids such as acetic acid, propionic acid, butyric acid, and valeric acid; hydroxy acids such as lactic acid, malic acid, and citric acid; dicarboxylic acids such as malonic acid, succinic acid, fumaric acid, and maleic acid; polycarboxylic acids such as polyacrylic acid and polymaleic acid; and amino acids such as arginine, histidine, and lysine.

[0101] Examples of the polyoxyalkylene compound include polyalkylene glycol and polyoxyalkylene derivatives.

[0102] Examples of the polyalkylene glycol include polyethylene glycol, polypropylene glycol, polybutylene glycol, etc. The polyalkylene glycol is preferably at least one selected from the group consisting of polyethylene glycol and polypropylene glycol, and more preferably polyethylene glycol.

[0103] The polyoxyalkylene derivative is, for example, a compound in which a functional group or a substituent is introduced into a polyalkylene glycol, or a compound in which a polyalkylene oxide is added to an organic compound. Examples of the functional group or the substituent include an alkyl ether group, an alkylphenyl ether group, a phenyl ether group, a styrenated phenyl ether group, a glyceryl ether group, an alkylamine group, a fatty acid ester group, and a glycol ester group. Examples of the polyoxyalkylene derivatives include polyoxyethylene alkyl ethers, polyoxyethylene bisphenol ethers (e.g., BA diol series manufactured by Nippon Emulsifier Co., Ltd.), polyoxyethylene styrenated phenyl ethers (e.g., Emulgen series manufactured by Kao Corporation), polyoxyethylene alkylphenyl ethers (e.g., Noigen EA series manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.), polyoxyalkylene polyglyceryl ethers (e.g., SC-E series and SC-P series manufactured by Sakamoto Yakuin Kogyo Co., Ltd.), polyoxyethylene sorbitan fatty acid esters (e.g., Sorgen TW series manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.), polyoxyethylene fatty acid esters (e.g., Emanon series manufactured by Kao Corporation), polyoxyethylene alkylamines (e.g., Amiradine D manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.), and other compounds to which polyalkylene oxides are added (e.g., Surfynol 465 manufactured by Nissin Chemical Industry Co., Ltd., and TMP series manufactured by Nippon Emulsifier Co., Ltd.).

[0104] The so-called "water-soluble polymer" is defined as a polymer that dissolves 0.1 g or more relative to 100 g of water. The polymer equivalent to the polyoxyalkylene compound is not included in the "water-soluble polymer". There are no particular restrictions on water-soluble polymers, and examples thereof include: acrylic polymers such as polyacrylamide and polydimethylacrylamide; polysaccharides such as carboxymethyl cellulose, agar, curdlan, dextrin, cyclodextrin, and pullulan; vinyl polymers such as polyvinyl alcohol, polyvinyl pyrrolidone, and polyacrolein; glycerol polymers such as polyglycerol and polyglycerol derivatives; polyethylene glycol, etc.

[0105] (Slurry or polishing fluid properties)

[0106] From the viewpoint of further improving the polishing speed of the insulating material, the lower limit of the pH of the slurry or polishing liquid involved in this embodiment is preferably 2.0 or more, more preferably 2.5 or more, more preferably 2.8 or more, especially preferably 3.0 or more, extremely preferably 3.2 or more, very preferably 3.5 or more, more preferably 4.0 or more, more preferably 4.2 or more, especially preferably 4.3 or more. From the viewpoint of further improving the storage stability of the slurry or polishing liquid, the upper limit of the pH is preferably 7.0 or less, more preferably 6.5 or less, more preferably 6.0 or less, especially preferably 5.0 or less, extremely preferably 4.8 or less, very preferably 4.7 or less, more preferably 4.6 or less, more preferably 4.5 or less, especially preferably 4.4 or less. From the viewpoint, the pH is more preferably 2.0 to 7.0. The pH is defined as the pH at a liquid temperature of 25°C.

[0107] The pH can be adjusted by an acid component such as an inorganic acid or an organic acid; an alkali component such as ammonia, sodium hydroxide, tetramethylammonium hydroxide (TMAH), imidazole, or an alkanolamine. A buffer may be added to stabilize the pH. A buffer solution (a liquid containing a buffer solution) may be prepared to add the buffer solution. Examples of such a buffer solution include acetate buffer solution and phthalate buffer solution.

[0108] The pH can be measured using a pH meter (e.g., Model PHL-40 manufactured by DKK East Asia Co., Ltd.). Specifically, for example, after the pH meter is calibrated at two points using a phthalate pH buffer (pH: 4.01) and a neutral phosphate pH buffer (pH: 6.86) as a standard buffer, the electrode of the pH meter is placed in the slurry or polishing liquid, and the value after stabilization for more than 2 minutes is measured. The liquid temperature is set to 25°C.

[0109] When the slurry or polishing liquid involved in this embodiment is used as a CMP polishing liquid, the constituent components of the polishing liquid can be made into a single-liquid polishing liquid and stored, or it can be made into a multi-liquid (for example, two-liquid) polishing liquid set in which the constituent components of the polishing liquid are divided into a first liquid and a second liquid in a manner that a first liquid containing abrasive grains and a liquid medium is mixed with a second liquid (additive liquid) containing an additive and a liquid medium to form a polishing liquid. The second liquid may also contain an oxidant, for example. The constituent components of the polishing liquid may also be made into a polishing liquid set divided into three or more liquids and stored.

[0110] In the polishing liquid set, the first liquid and the second liquid are mixed just before or during polishing to prepare the polishing liquid. In addition, the one-liquid polishing liquid can be prepared as a polishing liquid storage liquid with a reduced content of liquid medium and stored, and diluted with the liquid medium during polishing. The multi-liquid polishing liquid set can be prepared as a first liquid storage liquid and a second liquid storage liquid with a reduced content of liquid medium and stored, and diluted with the liquid medium during polishing.

[0111] <Grinding method>

[0112] The first mode of the polishing method (polishing method for substrate, etc.) involved in the present embodiment includes a process of polishing the polished surface using the polishing liquid obtained by the manufacturing method of the polishing liquid. The second mode of the polishing method (polishing method for substrate, etc.) involved in the present embodiment includes a polishing process of polishing the polished surface (polished surface of substrate, etc.) using the slurry (slurry before filtration) as a polishing liquid. According to the present embodiment, a high-speed polishing speed of the insulating material can be achieved. The slurry involved in the present embodiment can be used as a polishing liquid (CMP polishing liquid), for example. The polishing liquid in the polishing process can also be a polishing liquid obtained by mixing the first liquid and the second liquid in the polishing liquid group. The polished surface contains silicon oxide, for example.

[0113] According to the present embodiment, a slurry or a polishing liquid can be used for polishing a polished surface containing silicon oxide. According to the present embodiment, a slurry or a polishing liquid can be used for a flattening process of a substrate surface as a manufacturing technology for semiconductor elements. According to the present embodiment, a slurry or a polishing liquid can be used for a flattening process of an STI insulating material, a pre-metal insulating material, or an interlayer insulating material.

[0114] In the grinding process, for example, a base having a material to be ground is pressed against a grinding pad (grinding cloth) on a grinding platform, and slurry or polishing liquid is supplied between the material to be ground and the grinding pad, so that the base and the grinding platform are relatively moved to grind the grinding surface of the material to be ground. In the grinding process, for example, at least a portion of the material to be ground is removed by grinding.

[0115] Examples of the base body to be polished include a polished substrate. Examples of the polished substrate include a base body on which a material to be polished is formed on a substrate related to semiconductor element manufacturing (e.g., a semiconductor substrate on which an STI pattern, a gate pattern, a wiring pattern, etc. are formed). Examples of the material to be polished include insulating materials such as silicon oxide. The material to be polished may be a single material or may be a plurality of materials. When a plurality of materials are exposed on the polished surface, these may be regarded as the material to be polished. The material to be polished may be in the form of a film (polished film) or may be an insulating film such as a silicon oxide film.

[0116] The material to be polished (for example, insulating material such as silicon oxide) formed on such a substrate is polished using slurry or polishing liquid to remove excess parts, thereby eliminating the unevenness on the surface of the material to be polished, thereby obtaining an overall smooth surface of the material to be polished.

[0117] In the grinding method involved in this embodiment, as a grinding device, a common grinding device including a fixture that can hold a substrate having a grinding surface and a grinding platform to which a grinding pad can be attached can be used. A motor with a variable rotation speed is installed on the fixture and the grinding platform, respectively. As a grinding device, for example, a grinding device manufactured by Ebara Manufacturing Co., Ltd.: F-REX300 or a grinding device manufactured by APPLIED MATERIALS: MIRRA can be used.

[0118] As grinding pad, common nonwoven fabrics, foam, non-foam etc. can be used.As the material of grinding pad, resins such as polyurethane, acrylic resin, polyester, acrylic acid-ester copolymer, polytetrafluoroethylene, polypropylene, polyethylene, poly-4-methylpentene, cellulose, cellulose ester, polyamide (for example, nylon (trade name) and aromatic polyamide), polyimide, polyimide amide, polysiloxane copolymer, ethylene oxide compound, phenolic resin, polystyrene, polycarbonate, epoxy resin can be used.As the material of grinding pad, especially with respect to the viewpoint that grinding speed and flatness are more excellent, preferably at least one in the group consisting of foamed polyurethane and non-foamed polyurethane is selected.Preferably, grinding pad is implemented to accumulate slurry or grinding liquid and the like groove processing.

[0119] There is no restriction on the grinding conditions. In order to prevent the substrate from flying out, the upper limit of the rotation speed of the grinding platform is preferably 200 min -1 (min -1 = rpm), and from the viewpoint of easily suppressing the generation of grinding damage, the upper limit of the grinding pressure (processing load) applied to the substrate is preferably below 100 kPa. Preferably, during the grinding, the slurry or the polishing liquid is continuously supplied to the grinding pad by a pump or the like. The supply amount is not limited, and the surface of the grinding pad is preferably always covered by the slurry or the polishing liquid.

[0120] This embodiment is preferably used for grinding a polished surface containing silicon oxide. This embodiment can be suitably used in the formation of STI and the high-speed grinding of interlayer insulating materials. The lower limit of the grinding speed of the insulating material (e.g., silicon oxide) is preferably 150 nm / min or more, more preferably 200 nm / min or more, further preferably 300 nm / min or more, and particularly preferably 400 nm / min or more.

[0121] This embodiment can also be used in polishing of a pre-metal insulating material. Examples of the pre-metal insulating material include silicon oxide, phosphorus-silicate glass, boron-phosphorus-silicate glass, silicon oxyfluoride, and fluorinated amorphous carbon.

[0122] This embodiment can also be applied to materials other than insulating materials such as silicon oxide. Examples of such materials include: high dielectric constant materials such as Hf-based, Ti-based, and Ta-based oxides; semiconductor materials such as silicon, amorphous silicon, SiC, SiGe, Ge, GaN, GaP, GaAs, and organic semiconductors; phase change materials such as GeSbTe; inorganic conductive materials such as ITO; polymer resin materials such as polyimide-based, polybenzoxazole-based, acrylic-based, epoxy-based, and phenol-based materials.

[0123] This embodiment can be applied not only to film-shaped polishing objects, but also to various substrates made of glass, silicon, SiC, SiGe, Ge, GaN, GaP, GaAs, sapphire, plastic, etc.

[0124] This embodiment can be used not only in the manufacture of semiconductor elements, but also in the manufacture of image display devices such as TFT, organic EL, etc.; optical components such as photomasks, lenses, prisms, optical fibers, single crystal scintillators, etc.; optical elements such as optical switch elements, optical waveguides, etc.; light-emitting elements such as solid lasers, blue laser LEDs, etc.; magnetic storage devices such as disks and magnetic heads, etc.

[0125] Example

[0126] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to the following examples.

[0127] <Preparation of cerium oxide slurry A>

[0128] Particles containing cerium oxide (first particles, hereinafter referred to as "cerium oxide particles". Cerium oxide particles A) were mixed with ammonium dihydrogen phosphate (molecular weight: 97.99), a trade name, manufactured by Wako Pure Chemical Industries, Ltd., to prepare cerium oxide slurry A (pH: 7) containing 5.0 mass % (solid content) of cerium oxide particles. The amount of ammonium dihydrogen phosphate was adjusted to 1 mass % based on the total amount of cerium oxide particles.

[0129] An appropriate amount of cerium oxide slurry A was added to Microtrac MT3300EXII (trade name: manufactured by Microtrac BEL Co., Ltd.) to measure the average particle size of cerium oxide particles. The average particle size value shown was obtained as the average particle size (average secondary particle size). The average particle size of cerium oxide particles in cerium oxide slurry A was 145 nm.

[0130] An appropriate amount of cerium oxide slurry A was placed in DelsaNano C (trade name) manufactured by Beckman Coulter Co., Ltd., and the measurement was performed twice at 25° C. The average of the displayed zeta potentials was obtained as the zeta potential. The zeta potential of the cerium oxide particles in the cerium oxide slurry A was −55 mV.

[0131] <Preparation of cerium hydroxide slurry>

[0132] (Synthesis of Cerium Hydroxide)

[0133] 480 g of Ce(NH4)2(NO3) 650 mass % aqueous solution (manufactured by Nippon Chemical Industry Co., Ltd., trade name: CAN50 solution) was mixed with 7450 g of pure water to obtain a solution. Then, while stirring the solution, 750 g of imidazole aqueous solution (10 mass % aqueous solution, 1.47 mol / L) was added dropwise at a mixing speed of 5 mL / min to obtain a precipitate containing cerium hydroxide. The mixture was stirred at a temperature of 20°C and a stirring speed of 500 min. -1 Cerium hydroxide was synthesized under 30°C and stirred using a three-vane pitch paddle having a blade portion having a total length of 5 cm.

[0134] The obtained precipitate (containing cerium hydroxide) was centrifuged (4000 min -1 , 5 minutes), the liquid phase was removed by decantation, thereby implementing solid-liquid separation. After mixing 10 g of the particles obtained by solid-liquid separation with 990 g of water, the particles were dispersed in water using an ultrasonic cleaning machine to prepare a cerium hydroxide slurry (particle content: 1.0 mass %) containing particles containing cerium hydroxide (second particles. hereinafter referred to as "cerium hydroxide particles").

[0135] (Measurement of average particle size)

[0136] The average particle size (average secondary particle size) of the cerium hydroxide particles in the cerium hydroxide slurry was measured using the trade name: N5 manufactured by Beckman Coulter Co., Ltd., and the result was 10 nm. The measurement method is as follows. First, about 1 mL of a measurement sample (cerium hydroxide slurry. Aqueous dispersion) containing 1.0 mass % of cerium hydroxide particles is placed in a 1 cm square tank, and the tank is set in N5. The refractive index of the measurement sample information of the N5 software is set to 1.333, and the viscosity is set to 0.887 mPa·s. The measurement is performed at 25°C, and the displayed value is read as the unimodal size mean (UnimodalSize Mean).

[0137] (Measurement of Zeta Potential)

[0138] An appropriate amount of cerium hydroxide slurry was placed in DelsaNano C (trade name) manufactured by Beckman Coulter Co., Ltd., and the measurement was performed twice at 25° C. The average value of the displayed zeta potential was obtained as the zeta potential. The zeta potential of the cerium hydroxide particles in the cerium hydroxide slurry was +50 mV.

[0139] (Structural Analysis of Cerium Hydroxide Particles)

[0140] An appropriate amount of cerium hydroxide slurry was taken, vacuum dried to separate cerium hydroxide particles, and then washed thoroughly with pure water to obtain a sample. The obtained sample was measured by FT-IR ATR method. As a result, in addition to the observation of hydroxide ion (OH - ) peaks, we also observed peaks based on nitrate ions (NO3 - ) peak. In addition, the XPS (N-XPS) measurement of nitrogen was performed on the same sample, and the results showed that no NH4-based + The peak of nitrate ions was observed instead of the peak of cerium hydroxide particles. According to these results, it can be confirmed that the cerium hydroxide particles contain at least a portion of particles having nitrate ions bonded to the cerium element. In addition, since at least a portion of the cerium hydroxide particles contain particles having hydroxide ions bonded to the cerium element, it can be confirmed that the cerium hydroxide particles contain cerium hydroxide. According to these results, it can be confirmed that cerium hydroxide contains hydroxide ions bonded to the cerium element.

[0141] <Preparation of slurry>

[0142] (Example 1)

[0143] Using a two-blade stirring blade, 175 g of the cerium hydroxide slurry was mixed with 125 g of ion exchange water while stirring at a rotation speed of 300 rpm to obtain a mixed solution. Next, while stirring the mixed solution, 200 g of the cerium oxide slurry A was mixed with the mixed solution, and then ultrasonic waves were irradiated using an ultrasonic cleaning machine (device name: US-105) manufactured by SND Co., Ltd., while stirring. Thus, a test slurry containing composite particles including cerium oxide particles and cerium hydroxide particles in contact with the cerium oxide particles (cerium oxide particle content: 2.0 mass%, cerium hydroxide particle content: 0.35 mass%) was prepared.

[0144] (Example 2)

[0145] A test slurry containing composite particles including cerium oxide particles and cerium hydroxide particles in contact with the cerium oxide particles was prepared in the same manner as in Example 1 except that the amount of the cerium hydroxide slurry used was changed (cerium oxide particle content: 2.0 mass %, cerium hydroxide particle content: 0.3 mass %).

[0146] (Example 3)

[0147] Cerium oxide particles (cerium oxide particles B different from cerium oxide particles A) were mixed with ammonium dihydrogen phosphate (molecular weight: 97.99), a trade name, manufactured by Wako Pure Chemical Industries, Ltd., to prepare cerium oxide slurry B (pH: 7) containing 5.0 mass % (solid content) of cerium oxide particles. The amount of ammonium dihydrogen phosphate was adjusted to 1 mass % based on the total amount of cerium oxide particles. The average particle size and zeta potential of the cerium oxide particles in cerium oxide slurry B were measured in the same manner as cerium oxide slurry A, and the results were 148 nm and -55 mV.

[0148] Using a two-blade stirring blade, 150 g of the cerium hydroxide slurry was mixed with 150 g of ion exchange water while stirring at a rotation speed of 300 rpm to obtain a mixed solution. Next, while stirring the mixed solution, 200 g of the cerium oxide slurry B was mixed with the mixed solution, and then, while irradiating with ultrasound using an ultrasonic cleaning machine (device name: US-105) manufactured by SND Co., Ltd., stirring was performed. Thus, a test slurry containing composite particles including cerium oxide particles and cerium hydroxide particles in contact with the cerium oxide particles (cerium oxide particle content: 2.0 mass%, cerium hydroxide particle content: 0.3 mass%) was prepared.

[0149] (Example 4)

[0150] A test slurry containing composite particles including cerium oxide particles and cerium hydroxide particles in contact with the cerium oxide particles was prepared in the same manner as in Example 3 except that the amount of the cerium hydroxide slurry used was changed (cerium oxide particle content: 2.0 mass %, cerium hydroxide particle content: 0.5 mass %).

[0151] (Example 5)

[0152] Cerium oxide particles (cerium oxide particles C different from cerium oxide particles A and cerium oxide particles B), polyacrylic acid 5000 (weight average molecular weight: 5000) manufactured by Wako Pure Chemical Industries, Ltd., and ion exchange water were mixed to prepare cerium oxide slurry C (cerium oxide particle content: 5.0 mass %). The amount of polyacrylic acid added was adjusted to 1 mass % based on the total amount of cerium oxide particles. The average particle size and zeta potential of the cerium oxide particles in cerium oxide slurry C were measured in the same manner as cerium oxide slurry A, and the results were 145 nm and -55 mV.

[0153] Using a two-blade stirring blade, 150 g of the cerium hydroxide slurry was mixed with 150 g of ion exchange water while stirring at a rotation speed of 300 rpm to obtain a mixed solution. Next, while stirring the mixed solution, 200 g of the cerium oxide slurry C was mixed with the mixed solution, and then, while irradiating with ultrasound using an ultrasonic cleaning machine manufactured by SND Co., Ltd. (device name: US-105), stirring was performed. Thus, a test slurry containing composite particles including cerium oxide particles and cerium hydroxide particles in contact with the cerium oxide particles (cerium oxide particle content: 2.0 mass%, cerium hydroxide particle content: 0.3 mass%) was prepared.

[0154] (Comparative Example 1)

[0155] The cerium oxide slurry C was mixed with ion-exchanged water to prepare a test slurry containing cerium oxide particles (content of cerium oxide particles: 2.0 mass %).

[0156] (Comparative Example 2)

[0157] Cerium oxide particles (cerium oxide particles D different from cerium oxide particles A, cerium oxide particles B, and cerium oxide particles C), acetic acid (manufactured by Wako Pure Chemical Industries, Ltd.), and ion-exchanged water were mixed to prepare a test slurry containing cerium oxide particles (content of cerium oxide particles: 2.0 mass%). The amount of acetic acid added was 1.0 mass% based on the total amount of the cerium oxide particles.

[0158] (Comparative Example 3)

[0159] Colloidal cerium oxide particles having a primary particle size of 90 nm (cerium oxide particles E different from cerium oxide particles A, cerium oxide particles B, cerium oxide particles C, and cerium oxide particles D) were mixed with ion-exchanged water to prepare a test slurry containing cerium oxide particles (cerium oxide particle content: 2.0 mass % (solid content)).

[0160] (Comparative Example 4)

[0161] Colloidal cerium oxide particles having a primary particle size of 50 nm (cerium oxide particles F different from cerium oxide particles A, cerium oxide particles B, cerium oxide particles C, cerium oxide particles D, and cerium oxide particles E) were mixed with ion-exchanged water to prepare a test slurry containing cerium oxide particles (cerium oxide particle content: 2.0 mass % (solid content)).

[0162] <Average particle size of abrasive grains>

[0163] An appropriate amount of each test slurry was placed in Microtrac MT3300EXII (trade name: Microtrac BEL Co., Ltd.) to measure the average particle size of the abrasive. The average particle size value shown was obtained as the average particle size (average secondary particle size) of the abrasive. The measurement results are shown in Table 1.

[0164] <Rsp value>

[0165] The content of the abrasive grains in the test slurry was adjusted with ion exchange water as needed, thereby obtaining a measurement sample having an abrasive grain content (total amount of abrasive grains) of 2.0 mass %. Next, 2 mL of the measurement sample was added to an NMR tube, and the tube was placed in a pulse NMR particle interface characteristic evaluation device (manufactured by Rufuto Co., Ltd., Japan, trade name: Acron Area). Then, the pulse NMR measurement was performed under the following conditions, thereby obtaining the relaxation time Tav (average value of 5 measurements).

[0166] Set temperature: 25℃

[0167] Number of measurements: 5 times

[0168] After adding 7.5 g of the above-mentioned measurement sample to a 16 mm (inner diameter) × 76 mm long tube, the tube was placed in a centrifuge (manufactured by Beckman Coulter Co., Ltd., trade name: Optima MAX-TL). 5 G (236228G) was centrifuged at a setting temperature of 25° C. for 50 minutes, and about 4 mL of the supernatant was collected. Next, the supernatant was used to perform pulse NMR measurement in the same manner as above to obtain the relaxation time Tb.

[0169] The Rsp value was calculated from the above formula (1) using the obtained relaxation time Tav and relaxation time Tb. The Rsp value is shown in Table 1.

[0170] <Removal rate of coarse particles>

[0171] (Filtration of slurry)

[0172] The content of the abrasive grains in the test slurry was adjusted with ion exchange water as needed, thereby preparing a measurement sample 200 g having an abrasive grain content (total amount of abrasive grains) of 2.0 mass %. The measurement sample was placed in a cylindrical simple filtration device equipped with a 47 mm Φ disc filter (trade name: SCP-005, filter material: polypropylene, nominal pore size: 0.5 μm) manufactured by Roki Techno Co., Ltd., and then, the measurement sample (filtrate) passing through the filter was recovered by pressure feeding at 0.2 MPa. The slurry was passed through a single filter once without circulating treatment, thereby filtering.

[0173] (Determination of removal rate)

[0174] 10 g of the measurement sample (each measurement sample before and after filtration) and 90 g of ion exchange water were added to a 100 mL container, thereby diluting the measurement sample 10 times, and then the container was placed on a mixing rotor. The measurement sample was diluted as described above from the perspective of adjusting to a range lower than the upper limit of the measurement limit of the number of coarse particles in the measuring device. Secondly, it was stirred at a speed of 100 rpm for 10 minutes. Next, the above container was quietly placed in a light-shielded liquid particle sensor (device name: KS-71) manufactured by Rion Co., Ltd., and then the number of coarse particles of a size (particle size) of 3 μm or more before and after filtration was measured under the following measurement conditions (LPC: Large Particle Counts. Average value of 5 measurements). Based on the number of coarse particles before and after filtration of the measurement sample, the removal rate of coarse particles was calculated (removal rate of coarse particles [%] = (1-(LPC [pieces / mL] after filtration) / (LPC [pieces / mL] before filtration)) × 100). Table 1 shows the measurement results.

[0175] Measurement volume: 10mL / time

[0176] Flow rate: 60mL / min

[0177] Number of measurements: 5 times

[0178] In addition, the removal rate of coarse particles was measured under the same conditions as above for the ion exchange water used for adjusting the content of the abrasive after filtration, and it was confirmed that the removal rate of coarse particles was 50% or less, and the content of coarse particles in the ion exchange water was small. This confirmed that the LPC was not over-evaluated compared with the true value due to the mixing of coarse particles in the ion exchange water used for preparing the removal rate measurement sample and foreign matter attached to the container.

[0179] <CMP Evaluation>

[0180] Ion exchange water was added to the filtrate obtained by the same filtration as above to obtain a CMP polishing liquid having an abrasive content (total amount of abrasive particles) of 0.1 mass %. A substrate to be polished was polished under the following polishing conditions using this CMP polishing liquid.

[0181] [CMP polishing conditions]

[0182] Polishing device: MIRRA (manufactured by APPLIED MATERIALS)

[0183] Grinding liquid flow rate: 200mL / min

[0184] Substrate to be polished: A substrate to be polished having a 2 μm-thick silicon oxide film formed by plasma CVD on a silicon substrate was used as a blanket wafer without a pattern formed thereon.

[0185] Polishing pad: foamed polyurethane resin with independent cells (manufactured by Dow Chemical Co., Ltd., Japan, model IC1010)

[0186] Grinding pressure: 13kPa (2.0psi)

[0187] Rotation speed of the polished substrate and polishing platform: polished substrate / polishing platform = 93 / 87rpm

[0188] Grinding time: 1 minute

[0189] Wafer cleaning: After the CMP process, the wafer is cleaned with water while applying ultrasonic waves, and then dried in a spin dryer.

[0190] The polishing rate (SiO2RR) of the silicon oxide film polished and cleaned under the above conditions was calculated by the following formula. The results are shown in Table 1. The film thickness difference of the silicon oxide film before and after polishing was calculated using an optical interference film thickness measuring device (manufactured by Filmetrics Co., Ltd., trade name: F80).

[0191] Polishing rate (RR) = (thickness difference of silicon oxide film before and after polishing [nm]) / (polishing time: 1 [minute])

[0192] [Table 1]

[0193]

Claims

1. A slurry comprising abrasive particles and a liquid medium, wherein: The abrasive grains include first particles and second particles in contact with the first particles. The first particle contains cerium oxide, The second particle contains a cerium compound, The Rsp value calculated by the following formula (1) is 1.60 or more, Rsp=(Tb / Tav)-1 (1) Wherein, Tav represents the relaxation time of the slurry obtained by pulse NMR measurement when the content of the abrasive is 2.0 mass %, and the unit of the relaxation time Tav is ms; Tb represents the centrifugal acceleration of 2.36×10 5 G: The relaxation time of the supernatant obtained by centrifuging the slurry for 50 minutes using pulse NMR measurement, wherein the unit of the relaxation time Tb is ms.

2. The slurry according to claim 1, wherein The Rsp value is 1.80 or more.

3. The slurry according to claim 1, wherein The Rsp value is 2.00 or more.

4. The slurry according to claim 1, wherein The Rsp value is 2.20 or more.

5. The slurry according to claim 1, wherein The Rsp value is 2.40 or more.

6. The slurry according to claim 1, wherein The Rsp value is 10.0 or less.

7. The slurry according to claim 1, wherein The particle size of the second particles is smaller than the particle size of the first particles.

8. The slurry according to claim 1, wherein The average particle size of the first particles is 15 to 1000 nm.

9. The slurry according to claim 1, wherein The average particle size of the first particles is 40 nm or more.

10. The slurry according to claim 1, wherein The average particle size of the first particles is 400 nm or less.

11. The slurry according to claim 1, wherein The average particle size of the second particles is 1 to 50 nm.

12. The slurry according to claim 1, wherein The average particle size of the second particles is 3 nm or more.

13. The slurry according to claim 1, wherein The average particle size of the second particles is 15 nm or less.

14. The slurry according to claim 1, wherein The average particle size of the abrasive particles is 16 to 1050 nm.

15. The slurry according to claim 1, wherein The average particle size of the abrasive grains is 100 nm or more.

16. The slurry according to claim 1, wherein The average particle size of the abrasive grains is 300 nm or less.

17. The slurry according to claim 1, wherein The first particles have a negative zeta potential, and the second particles have a positive zeta potential.

18. The slurry according to any one of claims 1 to 17, wherein The cerium compound includes cerium hydroxide.

19. The slurry according to claim 18, wherein The content of the cerium hydroxide in the abrasive grains is 3 to 50% by mass based on the entire abrasive grains.

20. The slurry according to claim 18, wherein The content of the cerium hydroxide in the abrasive grains is 5 mass % or more based on the entire abrasive grains.

21. The slurry according to claim 18, wherein The content of the cerium hydroxide in the abrasive grains is 10% by mass or more based on the entire abrasive grains.

22. The slurry according to claim 18, wherein The content of the cerium hydroxide in the abrasive grains is 20 mass % or less based on the entire abrasive grains.

23. The slurry according to claim 18, wherein The content of the cerium hydroxide in the abrasive grains is 15 mass % or less based on the entire abrasive grains.

24. The slurry according to claim 18, wherein The content of the cerium hydroxide is 0.05 to 5% by mass based on the total mass of the slurry.

25. The slurry according to claim 18, wherein The content of the cerium hydroxide is 0.1% by mass or more based on the total mass of the slurry.

26. The slurry according to claim 18, wherein The content of the cerium hydroxide is 0.2 mass % or more based on the total mass of the slurry.

27. The slurry according to claim 18, wherein The content of the cerium hydroxide is 0.3% by mass or more based on the total mass of the slurry.

28. The slurry according to claim 18, wherein The content of the cerium hydroxide is 0.35 mass % or more based on the total mass of the slurry.

29. The slurry according to claim 18, wherein The content of the cerium hydroxide is 0.5 mass % or less based on the total mass of the slurry.

30. The slurry according to claim 18, wherein The content of the cerium hydroxide is 0.4 mass % or less based on the total mass of the slurry.

31. The slurry according to any one of claims 1 to 17, wherein The content of the cerium oxide in the abrasive grains is 50 to 97% by mass based on the entire abrasive grains.

32. The slurry according to any one of claims 1 to 17, wherein The content of the cerium oxide in the abrasive grains is 80 mass % or more based on the entire abrasive grains.

33. The slurry according to any one of claims 1 to 17, wherein The content of the cerium oxide in the abrasive grains is 85 mass % or more based on the entire abrasive grains.

34. The slurry according to any one of claims 1 to 17, wherein The content of the cerium oxide in the abrasive grains is 95 mass % or less based on the entire abrasive grains.

35. The slurry according to any one of claims 1 to 17, wherein The content of the cerium oxide in the abrasive grains is 90 mass % or less based on the entire abrasive grains.

36. The slurry according to any one of claims 1 to 17, wherein The content of the cerium oxide is 0.05 to 10% by mass based on the total mass of the slurry.

37. The slurry according to any one of claims 1 to 17, wherein The content of the cerium oxide is 1% by mass or more based on the total mass of the slurry.

38. The slurry according to any one of claims 1 to 17, wherein The content of the cerium oxide is 3% by mass or less based on the total mass of the slurry.

39. The slurry according to any one of claims 1 to 17, wherein The content of the abrasive grains is 0.01 to 10% by mass based on the total mass of the slurry.

40. The slurry according to any one of claims 1 to 17, wherein The content of the abrasive grains is 1% by mass or more based on the total mass of the slurry.

41. The slurry according to any one of claims 1 to 17, wherein The content of the abrasive grains is 2% by mass or more based on the total mass of the slurry.

42. The slurry according to any one of claims 1 to 17, wherein The content of the abrasive grains is 5% by mass or less based on the total mass of the slurry.

43. The slurry according to any one of claims 1 to 17, wherein The content of the abrasive grains is 3% by mass or less based on the total mass of the slurry.

44. A method for producing a polishing liquid, comprising the step of filtering the slurry according to any one of claims 1 to 43.

45. A polishing method comprising the step of polishing a surface to be polished using the polishing liquid obtained by the method for producing the polishing liquid according to claim 44.

46. ​​The grinding method according to claim 45, wherein: The polished surface includes silicon oxide.

Citation Information

Patent Citations

  • Polishing method

    JP1996022970A

  • Cerium oxide abrasive agent and polishing method of substrate

    JP1998106994A

  • Method for producing polishing agent and polishing agent

    JP2006249129A

  • Method for producing abrasive grains, method for producing slurry, and method for producing polishing liquid

    WO2012070544A1

  • CMP polisher and polishing method using the same

    JP2017203076A